2009
DOI: 10.1016/j.jbiomech.2009.05.037
|View full text |Cite
|
Sign up to set email alerts
|

Age-related mechanical work expenditure during normal walking: The Baltimore Longitudinal Study of Aging

Abstract: The aim of this cross sectional study was to delineate age-associated kinematic and kinetic gait patterns of normal walking, and to test the hypothesis that older adults exhibit gait patterns that reduce generative mechanical work expenditures (MWEs). We studied 52 adult Baltimore Longitudinal Study of Aging participants (means age 72 ± 9, from 60 to 92 years) who could walk 4-meters unaided. 3-dimensional kinematic and kinetic parameters assessed during rotation-defined gait periods were used to estimate MWEs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
50
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 23 publications
3
50
1
3
Order By: Relevance
“…48-49 Interestingly, while the standing posture only revealed differences with the severe OA group, differences between the younger and older asymptomatic groups and differences between the moderate and severe OA groups were detected during walking. This higher sensitivity during a dynamic activity supported the idea that decrease in motor control, 9,12,29,46 muscle strength 24,37 and soft-tissue properties 27,45 could be primary factors for the functional knee differences observed in this study. The importance of these three factors over swelling or pain was further strengthened by the fact that extension differences were noticed between two asymptomatic groups, which were equally free of swelling and pain.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…48-49 Interestingly, while the standing posture only revealed differences with the severe OA group, differences between the younger and older asymptomatic groups and differences between the moderate and severe OA groups were detected during walking. This higher sensitivity during a dynamic activity supported the idea that decrease in motor control, 9,12,29,46 muscle strength 24,37 and soft-tissue properties 27,45 could be primary factors for the functional knee differences observed in this study. The importance of these three factors over swelling or pain was further strengthened by the fact that extension differences were noticed between two asymptomatic groups, which were equally free of swelling and pain.…”
Section: Discussionsupporting
confidence: 85%
“…So it is also possible that they offer more options for adaptation since both feet are in contact with the ground during that time, thus reducing the consequences of functional adaptations on balance and gait performance. 9,46 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, humans may be able to choose more conservative gait strategies in which greater active control of leg motion is used, decreasing metabolic economy but increasing stability (lowering the risk of falling). Indeed, several investigators have suggested that the decreased metabolic economy of walking in many clinical populations is partially due to an increased focus on maintaining stability (Zamparo et al, 1995;Hoffman et al, 1997;Donelan et al, 2001;Mian et al, 2006;Ko et al, 2009;Reisman et al, 2009), which would correspond to a more conservative gait pattern on our theoretical figure.…”
Section: Introductionmentioning
confidence: 91%
“…Although there are studies that show the principles and phases present in the walk of a person [1] [2] [3] [4], it is affected in every person by numerous factors, including health [5] [6], age [7] [8] [9], the physical state [10], and gender [11]. Being able to measure and quantify the variables involved in the move-ments of the human body is justified in three main research categories [12]: physiology and health, computational, and robotics.…”
Section: Introductionmentioning
confidence: 99%